Recent Japanese philosophical thought 1862-1996 a survey : including a new survey by Baoshi Yamawaki, The philosophical thought of Japan from 1963 to 1996 - Piovesana, Gino K. 1917-; Yamawaki, Naoshi 1949- (Routledge Taylor & Francis Group, 2016)
Piovesana's famous survey is republished with an additional chapter by Naoshi Yamawaki to cover the intervening years up to 1996. It continues to be the only introduction to Japanese thinkers and philosophical thought covering the period of Japan's 'modern' era.